Backing the right horse: Entry versus fixed costs subsidies - Oke Röhe; Nikolai Stähler (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper provides a tractable dynamic stochastic general equilibrium framework with endogenous firm creation and destruction and variable technology utilization to analyze the macroeconomic impact of entry costs and fixed cost subsidies. Based on this setup, we revisit empirical and theoretical evidence on the macroeconomic effects of competition-enhancing industrial policies to shed light on the causes of the in part ambiguous results found in the literature. Our simulations confirm the findings of a potentially beneficial impact of both entry costs and fixed cost subsidies on output and employment. The welfare effects, however, turn out to be less clear cut and critically depend on the relative importance of several channels. In particular, our findings highlight the key role of business dynamism and its implications for productivity in determining the welfare effects of the respective policy measurers. Our results therefore illustrate the importance of considering sector-specific characteristics in the context of competitive-friendly industrial policies.
Keywords: H25; L52; E20; E62; L10; O30; 330; Industrial policies; Endogenous firm dynamics; Technology utilization; DSGE models